PELAYANAN ROOM BOY HOUSEKEEPING DEPARTMENT DI KTM RESORT - Siti Mariyam; Siti Sofro Sidiq (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Batam is a city that has many tourist destinations and accommodations such as hotels and resorts, one of which is the 3-star KTM Resort, which is located at Colonel Soegiono, Tanjung Pinggir, 29432 Sekupang, Riau Islands, Indonesia. KTM Resort was established in 2002 and the name of the KTM resort was taken from the name of the owner of KTM namely "KOH TIAT MENG" but, on September 7, 2017 the name KTM no longer uses the owner's name, but "KNOWLEGDE TEAM MAINDFULL" which means knowledge of the work team. The research design uses Quantitative Descriptive with the population of guests who visit and sample using the Non Probality Sampling technique with the Accidental Sampling method and this sample amounts to 60 people. Data collection is done by means of observation, interviews, documentation and questionnaires. Based on the results of the research of the 5 variables (Reability, Responsiveness, Assurance, Empathy, and Tangible) it can be concluded that there are 2.290 in the Good category.  Keywords: Room Boy Tasks, Responses, Service quality